Thermodynamic feasibility study of a suggested portable personal micro trigeneration system based on micro-gas turbine and micro-absorption chiller. (5th November 2018) - Adhami, Hozhabr; Khalilarya, Shahram; Jafarmadar, Samad; Ebrahimi, Masood
Highlights: A personal portable micro-CCHP is proposed. The overall weight of the system is about 14 kg. The system is designed for extremely hot and cold conditions. The system ability for multi-person utilization is investigated as well. Abstract: Combined cooling, heating and power (CCHP) which is also called trigeneration can be designed and manufactured in diverse scales and applications. In the present paper a single person portable micro CCHP system based on a micro-gas turbine and micro-absorption chiller is proposed and its performance is analyzed under different operational conditions. People under attack of war or natural disasters such as earthquake can use this system. A thermodynamic model is introduced to evaluate the personal energy demands at different ambient conditions. Then a micro-gas turbine is designed to produce 20 W electricity at speed of 200000 rpm and ambient temperature of 50 °C. In the next step the 500 W-class ultra-micro gas turbine (UMGT), is simulated as prime mover to estimate the cycle performance. LPG is the main fuel and the CCHP performance under extremely cold /hot weather is evaluated thermodynamically for three load management strategies. The maximum efficiency and minimum fuel consumption were related to the following hybrid electrical and thermal load strategy. In this case the maximum single-person CCHP efficiency was about 29% and fuel consumption was about 0.0645 g r · s - 1 of LPG at ambient temperature of 50 °C. The number of people who their energy demand was provided became maximum when following electrical load. The weight of the CCHP system is estimated to be less than 15 kg that is easily portable by a single grown person.